Lithuanian and Poland resistance movenment in 1942–1945: connection and difference. - Bubnys, Arūnas (Genocidas ir rezistencija, 2000)
During the Nazi occupation, Lithuanian–Polish hostility was almost equivalent to the war of 1919–1921 and manifested itself in a variety of forms: from domestic conflicts to open escalation. The most important cause of the Lithuanian–Polish conflict was the question of the national and administrative subordination of Vilnius. During the German occupation (1941–1944), the Vilnius region belonged to the General District of Lithuania. In addition to the German occupation authorities, there was also a Lithuanian administration – county and municipal self-government. After Lithuania regained Vilnius in 1939, the number of Lithuanian officials, teachers, policemen, priests, and other professions gradually increased in eastern Lithuania. Although during the Nazi occupation neither Lithuanians nor Poles were the real owners of Vilnius, there was a covert and sometimes open struggle for influence in Vilnius region.
Keywords: Lithuania; Poland; German occupation; antinazi resistance; Vilnius region